The role of spirituality in coping experience of muslim patients suffering from cervical cancer - Hernandia Distinarista; Tutik Rahayu (Universitas Muhammadiyah Semarang, 2022)
Psychological problems arise in cervical cancer patients because of the stages of management that must be followed since the patient performs an examination, makes a diagnosis, and during therapy that takes time which will not appear again. Some studies in cervical cancer patients have focused on morbidity or mortality more because of the risk of depression. The purpose of this study was to describe the condition of the spiritual role in the coping muslim patient suffering from cervical cancer undergoing chemotherapy. This study used a hermeneutic phenomenology method, involving six cervical cancer participants with chemotheraphy. Data were collected by semi-structured interviews which were then transcribed. Data analysis using content analysis. In the study, two themes were found, namely cervical cancer patients performing mahdhah worship, and performing ghairu mahdhah worship during cervical cancer treatment. The results of this study indicate that Muslim patient suffering from cervical cancer apply mahdah and ghairu mahdhah worship while undergoing cervical cancer treatment.